Mitigation of replant disease by mycorrhization in horticultural plants: A review - Lü Li-Hui; Wu Qiang-Sheng (Folia Horticulturae, 2018)
Replant disease refers to the result of monoculture-continuous repetitive planting of congeneric crops or coordinal crops in the same soil for many years. Such disease is recognized as one of the main limiting factors affecting plant growth and production of horticultural plants in many countries. As a result, replant disease in horticultural plants has become a world problem in agriculture and also a bottleneck restricting the sustainable development of agriculture. In general, replant disease results in unfavorable growth of horticultural plants, which is due to allelopathy, autotoxicity, and the imbalance of both soil physical-biochemical traits and soil microflora. An environmentally friendly contribution to this could be bio-controlled by beneficial microorganisms. Arbuscular mycorrhizal fungi, one of soil-inhabiting fungi, can form a symbiotic association in roots to mitigate the negative effects of replant disease in many horticultural plants. Moreover, arbuscular mycorrhizal fungi do not produce any environmental pollution in soils and are a potential biological control. The soil fungi could regulate better morphological, physiological and molecular levels in plants to respond to the disease. This review mainly outlined the current knowledge in mycorrhizal mitigation of replant disease in horticultural plants, which appears to be a promising strategy to improve growth of horticultural plants in replant soils.